The Religious Context in Explaining Public Support for the European Union. (2nd December 2014) - Scherer, Margarete
Abstract This article examines contextual explanations for public support for European integration. Apart from economic and identity‐based theories, there may also be a religious dimension that could help to explain why some countries are principally pro‐European while others are largely eurosceptic. It is argued that differences between nations are embedded in historical alliances between Catholic and Protestant denominations and political systems. Hierarchical linear model analyses of data from the European Social Survey (ESS) show that: (1) citizens from Catholic countries are more likely to support European unification than the inhabitants of Protestant countries; and (2) this effect conditions the individual‐level effect of welfare attitudes. This suggests that in Protestant countries support for welfare redistribution is associated with low support for the EU, while in Catholic countries support for welfare redistribution is associated with high support for the EU.